2010
DOI: 10.1111/j.1600-0501.2009.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich fibrin membranes as scaffolds for periosteal tissue engineering

Abstract: PRF appears to be superior to collagen (Bio-Gide) as a scaffold for human periosteal cell proliferation. PRF membranes are suitable for in vitro cultivation of periosteal cells for bone tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 36 publications
3
149
0
5
Order By: Relevance
“…Also, the present Meta-Analysis found that CAF + PRF did not increase %RC when compared to CAF alone (p = 0.60). In regards to healing and pain assessment, all the three studies that included HI and pain in their outcomes consistently reported a significant reduction in pain for the first 5-7 days and faster healing in the PRF intervention when compared to the use of CTG or EMD, which was consistent with numerous studies describing faster healing potential of growth factors in regenerative procedures [32,38,39,[47][48][49][50][51][52]. This finding is explained by PRF characteristics, when compared to other forms of blood derived growth factors like PRP, in the slow release of growth factors over a period of 10 days which is the time needed for revascularization and CT formation in a soft tissue regeneration procedure, while PRP was known for an earlier release of growth factors in the healing cascade [53][54][55].…”
Section: Discussionsupporting
confidence: 68%
“…Also, the present Meta-Analysis found that CAF + PRF did not increase %RC when compared to CAF alone (p = 0.60). In regards to healing and pain assessment, all the three studies that included HI and pain in their outcomes consistently reported a significant reduction in pain for the first 5-7 days and faster healing in the PRF intervention when compared to the use of CTG or EMD, which was consistent with numerous studies describing faster healing potential of growth factors in regenerative procedures [32,38,39,[47][48][49][50][51][52]. This finding is explained by PRF characteristics, when compared to other forms of blood derived growth factors like PRP, in the slow release of growth factors over a period of 10 days which is the time needed for revascularization and CT formation in a soft tissue regeneration procedure, while PRP was known for an earlier release of growth factors in the healing cascade [53][54][55].…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the phagocytosis of neutrophils and the enzymatic degradation process are modulated by FDP [8] and hence fibrin also plays an important role in immunity control. Studies have shown that PRF appears to be superior to collagen as a scaffold for human periosteal cell proliferation [9] and, rapid healing of the wound is observed without pain, dryness or purulent complications [7].…”
Section: Physiology Of Platelet Rich Fibrin (Prf)mentioning
confidence: 99%
“…Various pathological etiologies result in dysfunction of the oral tissues and creation of bony defects, thus affecting the quality of life in these patients. The pivotal goal in periodontal and maxillofacial tissue regeneration is to reconstruct these defects which led to the search of a biofuel [1]. Focus has constantly been on devising a "wonder material" that is most effective in its regenerative potential.…”
Section: Introductionmentioning
confidence: 99%